Functional Implication of Mitral Annular Disjunction in Mitral Valve Prolapse: A Quantitative Dynamic 3D Echocardiographic Study - Lee, Alex Pui-Wai; Jin, Chun-Na; Fan, Yiting; Wong, Randolph H L; Underwood, Malcolm J; Wan, Song (JACC. Cardiovascular imaging, 2017)
This study aimed to assess the hypothesis that mitral annular disjunction (MAD) is associated with abnormal annular dynamics due to decoupling of annular-ventricular function. MAD, defined as a separation between the atrial wall-mitral valve (MV) junction and left ventricular (LV) attachment, is a structural abnormality occurring in MV prolapse (MVP). Few data exist on the 3-dimensional (3D) geometry of MAD and its functional implication. A total of 156 subjects including 101 MVP patients (58 ± 11 years), 30 subjects with normal MV (57 ± 15 years), and 25 heart failure patients with functional mitral regurgitation (66 ± 10 years) were studied using real-time 3D transesophageal echocardiography. The spatial relation between atrial wall, MV, and LV attachment was examined for MAD. The 3D extent of MAD and annular dynamics were quantitatively assessed. The LV global longitudinal strain and basal circumferential strains were measured by speckle tracking echocardiography. MAD was evident in 42 MVP patients (42%), measuring 8.9 mm (6.3 to 10.7 mm), circumferentially spanning 87 ± 41°. Dynamically, normal and nondisjunctive annulus contracted and increased in a saddle shape during systole. In heart failure patients with functional mitral regurgitation, mitral annulus was dilated and relatively adynamic, probably related to poor LV function. In contrast, disjunctive annulus displayed paradoxical systolic expansion and flattening (p < 0.0001), despite preserved and comparable LV strains with normal patients. The 3D extent of MAD correlated significantly with abnormal annular dynamics and larger regurgitant orifice (p < 0.0001). In MVP patients without MAD, the LV global longitudinal strain correlated inversely with change in height (r = -0.61; p < 0.0001), whereas LV basal circumferential strain correlated with change in area (r = 0.61; p < 0.0001), but not in patients with MAD (p > 0.05). MAD is a common anatomic abnormality in MVP. The disjunctive annulus is decoupled functionally from the ventricle, leading to paradoxical annular dynamics with systolic expansion and flattening, and may thus require specific intervention.